Exploratory study on the application of laser-induced cavitation bubble in the treatment of fallopian tube obstruction - Dongdong Wang; Fang Yang; Weinan Gao; Yong Bi; Xuehong Zhu; Zhong Lin (PLoS ONE, 2025)
Significance: Globally, infertility affects 10–15% of couples, with Fallopian Tube Obstruction (FTO) being a principal cause. Current therapeutic options are inadequate, prompting a demand for effective, less invasive treatments with lower recurrence. Aim: The purpose of this study is to explore the feasibility of employing laser-induced cavitation bubbles (LICB) technology for the treatment of FTO and to experimentally ascertain the optimal laser parameters for this approach. Method: Utilizing an Er:YAG pulsed laser (2.94 μm, 200 μs pulse width, 10 Hz), laser energy was transmitted through a 450 μm sapphire fiber. The study involved 13 rats categorized into control, model, and experimental groups. The laser, with energies of 8.3 mJ, 12.7 mJ, and 15.3 mJ, was applied through the sapphire fibers. The assessment criteria incorporated Hematoxylin-Eosin (HE) staining of the fallopian tubes across all groups, evaluating tubal patency and wall damage to ascertain the most effective laser parameters. Results: In this experiment, the cumulative recanalization success rate in rat models of FTO treated with LICB was observed to be 75%. Specifically, a recanalization rate of 33.3% was achieved with the application of 8 mJ laser energy. The use of 12.7 mJ laser energy resulted in an increased success rate of 85.7%. However, while the application of 15.3 mJ laser energy achieved a 100% recanalization rate, it was accompanied by the formation of hemorrhagic spots on the fallopian tube walls, indicating thermal damage due to the higher energy levels. Optimal treatment parameters were identified as 12.7 mJ laser energy, 10 Hz frequency, and 10-second application. Conclusions: This research suggests that LICB technology can effectively clear fallopian tube obstructions while causing acceptable levels of damage. This indicates its potential as a valuable treatment method worthy of further research for facilitating tubal recanalization.